Bond durability assessment and long-term degradation prediction for GFRP bars to fiber-reinforced concrete under saline solutions - Yan, Fei; Lin, Zhibin (Composite structures, 2017)
This study presents the bond durability of glass fiber-reinforced polymer (GFRP) bars to fiber-reinforced concrete (FRC) exposed to saline solutions. Total 105 pullout specimens reinforced with steel and polyvinyl alcohol (PVA) fibers were prepared and immersed in the saline solutions at 50 and 70°C under 30, 45, and 60days, respectively. Their durability was quantified in terms of failure mode, adhesion stress as well as the bond strength. Test results revealed that the steel FRC samples exhibited the better bond durability than that of PVA FRC ones, when the same fiber volume fraction was used. Besides, the experimental data also aided to calibrate the analytical models, mBPE and CMR models, to better define the GFRP bond to FRC by considering the environmental effects. Also, a detailed procedure using Arrhenius law and time shift factor (TSF) methods was developed to predict the long-term bond degradation under different environmental temperatures and relative humidity. Degradation predictions over 75years showed the FRC with 1.0% steel fiber volume fraction will have 96.76%, 92.88%, and 74.47% bond strength retention under dry, moist, and saturated environments in cold regions, respectively; while these values will decrease to 95.83%, 90.85%, and 67.19% in warm regions, respectively.